Investigating English Lecturers' Strategies of Committing Online Written Corrective Feedback during Covid-19 Pandemic - Hanan, Ahmad; Firman, Edi; Terasne, Terasne (Universitas Pendidikan Mandalika, 2022)
Written corrective feedback is essential in the teaching of writing skills to help prospective teacher enhance their writing performance. Lecturers try to apply strategies in committing written corrective feedback in fully online learning. In addition, written corrective feedback can improve learners' metalinguistics, metacognition, teachers-learners interaction, and peer connection. Consequently, the present study will be aimed at investigating English lecturers' common practices and strategies in committing online written corrective feedback during Covid-19 pandemic at higher education. This study is classified as a qualitative study which is a descriptive qualitative study. It is chosen because the data of this study relates to opinions or attitudes in the form of lecturers' strategies in the teaching of writing skills and online corrective feedback. The data are elaborated in the form of words, phrases, sentences, and paragraphs. To attain the data, researchers use interview technique. There are five English lecturers involved in the current study. The data are analyzed by using qualitative processes which are data condensation, data display, and conclusion drawing or verification. The novelty of this study lies on written feedback, written corrective feedback, and online written corrective feedback. Due to Covid-19 pandemic, the teaching-learning process is done in fully online learning.